The Supply of Rheumatology Specialist Care in Real Life. Results of a Nationwide Survey and Analysis of Supply and Needs - Puchner, Rudolf; Vavrovsky, Anna; Pieringer, Herwig; Hochreiter, Ronald; Machold, Klaus P. (Frontiers in Medicine, 2020)
Objectives: To study the balance between supply and demand for rheumatology care in Austria. In addition, to investigate rheumatologists’ work-hours, the amount of time rheumatologists dedicate to care for patients with rheumatic and musculoskeletal diseases (RMD), with non-RMD problems, and other professional activities such as research, teaching, and administration. Methods: A questionnaire covering aspects of professional activities was sent to all 215 rheumatologists registered with the Austrian Medical Association. The data collected were set in relation to the demand calculated on the basis of recommendations put forward by the German society of rheumatology. Results: 149 of the 215 rheumatologists (69.0%) responded. Median weekly working time was 50 hours (IQR 45-60). 47.4% of the working time was spent for care of patients with RMD. The remaining time was dedicated to patients with non-rheumatic diseases (19.6%), research and teaching (8.4%), and administration (24.5%). The number of full-time equivalents (FTE, based on a 40-hour work-week) available for rheumatology care thus was calculated to be 178.5.. Based on disease prevalence/incidence estimates and on the time allocation results of this survey, our study resulted in a need of 4.26 rheumatologists per 100.000 adult inhabitants (308.7 for an adult population of 7.03x106). Conclusion: The study demonstrated a substantial mismatch between the available supply and the need for rheumatology care. The results of our study are a conservative estimate which should be taken into consideration for future healthcare workforce planning. In particular, the rising demand for rheumatologists should be met by increasing the numbers of those specialists.